2007
DOI: 10.1088/0953-8984/19/46/466212
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for an intermediate phase in the multiferroic YMnO3

Abstract: Abstract.We have studied YMnO 3 by high-temperature synchrotron X-ray powder diffraction, and have carried out differential thermal analysis and dilatometry on a single crystal sample. These experiments show two phase transitions at about 1100K and 1350K, respectively. This demonstrates the existence of an intermediate phase between the room temperature ferroelectric and the high temperature centrosymmetric phase. This study identifies for the first time the different high-temperature phase transitions in YMnO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
56
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 25 publications
12
56
2
Order By: Relevance
“…Fennie et al [25] and Kim et al [23] supported the path of a single transition (at ∼1270 K), driven by a K 3 order parameter which couples to a secondary zone centre order parameter (associated with − 2 ) to induce ferroelectricity. In contrast to this, some studies [14,24,26] have suggested one of the paths that involves an intermediate phase between the paraelectric P6 3 /mmc phase and the ferroelectric P6 3 cm phase. The most recent powder neutron diffraction data agree with the assessment of a single, continuous high temperature phase transition causing a tripling of the unit cell at ∼1258 K from P6 3 /mmc to polar P6 3 cm [15].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Fennie et al [25] and Kim et al [23] supported the path of a single transition (at ∼1270 K), driven by a K 3 order parameter which couples to a secondary zone centre order parameter (associated with − 2 ) to induce ferroelectricity. In contrast to this, some studies [14,24,26] have suggested one of the paths that involves an intermediate phase between the paraelectric P6 3 /mmc phase and the ferroelectric P6 3 cm phase. The most recent powder neutron diffraction data agree with the assessment of a single, continuous high temperature phase transition causing a tripling of the unit cell at ∼1258 K from P6 3 /mmc to polar P6 3 cm [15].…”
Section: Introductionmentioning
confidence: 93%
“…Of these materials YMnO 3 , with a layered structure with Y ions placed between sheets of corner sharing MnO 5 triangular bipyramids, has been of particular interest [9][10][11][12][13][14][15][16]. It is ferroelectric (FE) below ∼900-1300 K and antiferromagnetic (AFM) below ∼75 K [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these cases ferroelectricity has been claimed to emerge together with a trimerizing lattice distortion in a single-step transition 16,18,19 . In other cases these two features have been proposed to occur separately [10][11][12][13][14][15] . On the theoretical side, the two-transition scenario has initially been supported by density-functional-theory calculations 20 .…”
mentioning
confidence: 99%
“…After there has been some debate concerning the thermodynamic path occurring at the transition between the paraelectric P 6 3 /mmc (Z=2) and ferroelectric P 6 3 cm (Z=6) phases in YMnO 3 recent experimental and theoretical investigations agree in that the cell-tripled improper ferroelectric structure arises directly at the Curie temperature T C of about 1260 K. [1][2][3][4][5][6][7][8][9] A confirmation of this direct path is the observation of a ferroelectric domain pattern below T C consistent with the twodimensional-order-parameter symmetry associated with the K 3 zone-boundary phonon mode at k = ( 1 3 , 1 3 , 0). [10][11][12][13][14][15][16] The corresponding symmetry-breaking mechanism gives rise to a total of six domain states.…”
mentioning
confidence: 99%